Prevalence, clinical significance, and management of peripheral arterial disease in women: is there a role for postmenopausal hormone therapy? - Ramesh Mazhari; Judith Hsia (Vascular Health and Risk Management, 2005)
Ramesh Mazhari, Judith HsiaDivision of Cardiology, George Washington University, Washington, DC, USAAbstract: Peripheral arterial disease (PAD), like coronary heart disease, is a clinical manifestation of atherosclerosis and is associated with increased mortality. Although atherosclerotic cardiovascular disease is the leading cause of death for women as well as for men, PAD in women has received less attention than coronary heart disease or stroke. This paper reviews the prevalence of PAD, its risk factors, clinical significance, and management in women. One gender-specific therapeutic issue of particular interest to practitioners and the lay public is the role of postmenopausal hormone therapy. Prior to completion of the Heart and Estrogen/Progestin Replacement Study and the Women’s Health Initiative Hormone Trials, postmenopausal hormone therapy was believed to exert antiatherosclerotic effects and to thereby reduce coronary heart disease risk in women on the basis of case-control and cohort studies. This review particularly focuses on the role, if any, of postmenopausal hormone therapy for prevention or treatment of PAD, which was a pre-specified secondary outcome for these three randomized trials.Keywords: women, estrogen, peripheral arterial disease